I-V Characteristic at Different Depletion Region for CMOS PN Photodiode for Optical Communication Applications - Othman, Mohd Azlishah; M.Napiah, Zul Atfyi Fauzan; Ismail, Mohd Muzafar; Sulaiman, Hamzah Asyrani; Misran, Mohamad Harris; Meor Said, Maizatul Alice (2012)
In this paper, CMOS PN photodiode will be design and analyze for the application at 5GHz optical communication. The paper will be divided in several section; the theory of CMOS PN photodiode and design with analysis of IV characteristics of PN photodiode. A better understanding of the operation will be investigated through this. The PN photodiode will be design using Silvaco TCAD and will be characterize and experimental in IV Characteristic. The effects of IV characteristic will be analyzed in term of changes the width and light. Further understanding of IV characteristic will be presents in this paper. Keyword - PN photodiode, IV Characteristic, Silvaco TCAD.